Microhabitat and plant structure of Batrachospermum (Batrachospermales, Rhodophyta) populations in four streams of São Paulo State, southeastern Brazil - Necchi Jr., Orlando [UNESP] (Wiley, 1997)
Microhabitat and plant structure of seven Batrachospermum populations (four of Batrachospermum delicatulum (= Sirodotia delicatula), one of Batrachospermum macrosporum and two of the 'Chantransia' stage), including the influence of physical variables (current velocity, depth, irradiance and substratum), were investigated in four streams of São Paulo State, southeastern Brazil. The populations of B. delicatulum and the 'Chantransia' stage occurred under very diverse microhabitat conditions, which probably contributes to their wide spatial and seasonal distribution in Brazilian streams. Results suggest branch reconfiguration as a probable mechanism of adaptation to current velocity based on the occurrence of: (i) B. macrosporum (a large mucilaginous form with presumably little ability for branch reconfiguration) under lower current velocity than B. delicatulum; (ii) only dense plants in populations with high current velocities (> 60 cm s-1), whereas 53-77% of dense plants were seen in populations exposed to lower currents (< 40 cm s-1); (iii) positive correlations of plant length with internode length in populations under low current velocities and negative correlation in a population with high velocity (132 cm s-1); and (iv) negative correlations of current velocity with plant diameter and internode length in a population under high flow. This study, involving mainly dioecious populations, revealed that B. delicatulum displayed higher fertilization rates than B. macrosporum. A complementary explanation for a dioecious species to increase fertilization success was proposed consisting of outcrossing among intermingled male and female adjacent plants within an algal spot.
Keywords: Batrachospermum; Current velocity microhabitat; Plant structure; Stream